Diversification of crops: Assessment of managerial flexibility and economic impact on sugarcane medium-sized farms - Santos, David Ferreira Lopes [UNESP]; Gomes, Samara Marques [UNESP] (Frontiers, 2022)
The aim of this study is to assess the economic viability of a medium-sized sugarcane farm applying a diversification strategy, including the possibility of managerial flexibility in changing its portfolio over time. There is a theoretical gap in the economic evaluation of diversified production systems in farm space. We assessed one diversified structure for the sugarcane agricultural farm that included land areas dedicated to the rotational cultivation of soybean/corn, corn/peanut, and corn/green manure. We considered the managerial flexibility when replacing sugarcane culture. Primary and secondary data were used based on the agricultural context of São Paulo State, Brazil, where the modal profile of medium-sized producers in the region was defined with the support of technicians from the leading agricultural cooperative and sugarcane suppliers association. The results indicate that the diversification strategy for the investigated context generates: lower financial risk for the farm, higher potential return on investment, and higher economic value added.
Keywords: agribusiness; investment analysis; portfolio; Real Options Theory; rotational cultivation